THE INFLUENCE OF TREATMENT WITH CORDAFLEX-RETARD ON LIFE QUALITY OF PATIENTS WITH ARTERIAL HYPERTENSION - L. I. Katelnitskaya; I. V. Luzhetskaya; G. O. Treneva; S. G. Kechejieva; L. A. Mahova; N. A. Yelizarov; A. N. Yelizarov (Российский кардиологический журнал)
We studied the effectiveness and safety of administration of the extended-action calcium antagonist Nifedipin-Retard (Cordaflex-Retard, EGIS) in 30 patients with arterial hypertension of the 1st and 2nd degree. The study included general clinical examination, round-the-clock monitoring of the arterial pressure (AP) and of the heart rate (HR). Before the therapy and after 6 months of monitoring, examination was performed to assess the life quality and the risk factors, as well as the quantity and quality of health. Cordaflex-Retard was administered depending on the initial AP, in the daily dose of 20 to 40 mg during 24 weeks. We found not only hypotensive action with the AP level stabilization, but also reduction of the magnitude and the rate of the SAP morning rise, as well as a greater degree of the night dipping of the SAP and DAP, accompanied by improvement of the life quality.